Analisis Penggunaan Frame Markers, Transitions, dan Sequence Markers dalam Penulisan Ilmiah Mahasiswa - Elyana, Kukuh (Adjektiva: Educational Languages and Literature Studies, 2025)
This study investigates the use of interactive metadiscourse in the background sections of academic papers written by 38 undergraduate students enrolled in the General Compulsory Indonesian Language Course at Universitas Mulawarman in 2025. Grounded in Hyland’s (2005) metadiscourse framework, the research focuses on three key subcategories: frame markers, transitions, and sequence markers. A qualitative descriptive method was employed through document analysis to examine how students deploy these rhetorical strategies to construct coherence and guide readers through their arguments. Each student paper was manually analyzed for the presence and frequency of metadiscourse markers, with findings triangulated by course instructors for validation. The results reveal that most students utilized more than one type of interactive marker in their writing, with 29 students using frame markers and 28 students applying transitions. However, only one student incorporated sequence markers, indicating a limited awareness of this rhetorical device. The intensity of usage varied across individuals, ranging from 6 to 20 occurrences, suggesting differing levels of rhetorical competence and text organization. Students who used metadiscourse more frequently demonstrated stronger cohesion, while those with lower usage tended to produce less structured and more descriptive texts. This study highlights the importance of explicit instruction in academic writing, particularly in metadiscourse, to support students in developing effective rhetorical strategies. The findings offer practical implications for language instruction at the tertiary level and contribute to the broader understanding of how metadiscourse functions in the early stages of academic literacy development in non-English speaking contexts.